Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Computational investigation on the catalytic activity of Rh-6 and Rh4Ru2 clusters towards methanol activation - Ghatak, Kamalika; Sengupta, Turbasu; Krishnamurty, Sailaja; Pal, Sourav (Theoretical Chemistry Accounts, 2014)
Catalysis of molecular activation of small molecules through scission of strong chemical bonds is one of the major challenges faced by chemists. More specifically, activation of the strong C-H and O-H bonds of various alcohols, especially methanol, is one of the various important intermediate steps of key organic reactions. Our present work explores a suitable metal cluster catalyst towards methanol dissociation. In particular, we have examined the effect of ruthenium doping (Rh:Ru = 2:1) on the catalytic activity of Rh-6 cluster towards methanol dissociation. Density functional theory-based calculations illustrate two competitive pathways for methanol dissociation, which are via O-H and C-H bond breaking. Both the pathways are found to be energetically favourable in the presence of bimetallic and mono-metallic clusters. Importantly, energy barrier for O-H bond dissociation reduces considerably in doped cluster as compared to pure Rh-6 cluster and is smaller than the values reported for a number of other small metallic clusters.
Keywords: Bimetallic Clusters; Density Functional Theory (DFT); Doping; Methanol Activation; Rhodium Clusters